Steps of Distal Radical Gastrectomy for Carcinoma of the antrum and Roux-en-Y gastro-jejunostomy: A case presentation - Islam, Sardar Rezaul; Hanif, Mohammad; Vashkar, Shaikh Mahmud Kamal; Hossain, Shahadat (The Journal of Ad-din Women's Medical College, 2023)
A 75 year old man presented with gastric outlet obstruction with a history of vomiting and weight loss for a period of 4 months. He had severe electrolyte imbalance, anemia and malnutrition. CT-scan revealed a huge antral carcinoma occupying the distal half of stomach. Firstly, his anemia and electrolyte imbalance was corrected, followed by preoperative parenteral nutrition. Stapler assisted distal radical gastrostomy and Roux-y gastro-jejunostomy was performed. The patient had excellent post-operative recovery. He was discharged on resumption of oral feeding and referred to the oncologist for adjuvant therapy. This case report, is on steps of stapler assisted distal radical gastrectomy with high resolution operative picture from the Department of Surgery, AWMCH. The Journal of Ad-din Women's Medical College; Vol. 10 (1), Jan 2022; p 38-41